2022
DOI: 10.3390/antiox11102011
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Medium from H2O2-Preconditioned Human Adipose-Derived Stem Cells Ameliorates UVB-Induced Damage to Human Dermal Fibroblasts

Abstract: Human skin exposure to ultraviolet B (UVB) radiation can result in acute photodamage through oxidative modifications of cellular components and biomolecules involved in the metabolism of dermal cells. Recently, the therapeutic potential of human adipose-derived stem cells (hASCs) has been investigated as a novel strategy for photoprotection due to their pro-angiogenic properties, protective activity against oxidative stress and paracrine effect on dermal cells. To enhance these therapeutic properties, hASCs ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…28 Recent studies revealed that preincubating MSCs with a low concentration of H 2 O 2 can not only enhance their resistance to oxidative stress but also improve the antioxidant effects of their paracrine factors. 17,29 In line with the aforementioned studies, our research revealed that the EVs from H 2 O 2 -activated ADSCs exhibit significantly higher levels of antioxidant activity compared to EVs derived from unstimulated cells. It is noteworthy that the diabetic BMSCs stimulated with H 2 O 2 -activated EVs showed higher viability and osteogenic differentiation potential than the cells preincubated with normal EVs.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…28 Recent studies revealed that preincubating MSCs with a low concentration of H 2 O 2 can not only enhance their resistance to oxidative stress but also improve the antioxidant effects of their paracrine factors. 17,29 In line with the aforementioned studies, our research revealed that the EVs from H 2 O 2 -activated ADSCs exhibit significantly higher levels of antioxidant activity compared to EVs derived from unstimulated cells. It is noteworthy that the diabetic BMSCs stimulated with H 2 O 2 -activated EVs showed higher viability and osteogenic differentiation potential than the cells preincubated with normal EVs.…”
Section: Discussionsupporting
confidence: 84%
“…15,16 Previous research has demonstrated that preconditioning MSCs with moderate concentrations of H 2 O 2 not only enhances their resistance to oxidative stress but also amplifies the antioxidant effects of their paracrine factors. 17,18 However, it remains unclear whether stimulating MSCs with H 2 O 2 could enhance the antioxidant and anti-senescence capabilities of their EVs. 18 This study aimed to compare the impact of EVs from H 2 O 2 -stimulated adipose-derived stem cells (ADSCs) with those from untreated ADSCs on the senescence and osteogenic potential of diabetic bone marrow mesenchymal stem cells (BMSCs).…”
Section: Introductionmentioning
confidence: 99%
“…Critical information about physiological and toxic thresholds is lacking, and these may well be cell type specific. Interestingly, in the regenerative medicine field, cell preconditioning with short treatments of low doses of H2O2 are being put into practice to use the beneficial effects of ROS as therapeutic strategy [47][48][49]. Guided by these efforts, it is conceivable that, in the near future, oxidants and antioxidants will be carefully and timely dosed to rescue pathology without challenging the function of the other.…”
Section: Oxidative Stressmentioning
confidence: 99%